Avaliação de desempenho da cinza do bagaço de cana-de-açucar na produção de concretos - Souto, Jean Marcelo Fernandes (2010)
In recent years science has devoted considerable attention to global warming. The direct emission of carbon dioxide in the atmosphere has been identified as the main factor in destroying the ozone layer, with only the cement industry accounts for 07% of all CO2 emissions in the world. Aiming to reduce these levels of CO, and the consequences of global warming, research has been developed with the aim of reducing the volume of cement produced in the planet through mineral admixtures, especially the use of agro-industry waste (rice husk ash and bagasse ash - of - sugar), which in Brazil amounted to a volume of 3.5 million tons. The work that follows explores the effect of sugarcane bagasse ash - of - sugar, "in natura", with contents ranging between 05 and adding 30% in concrete class C30. The CBC, bagasse ash cane sugar was assessed by physical tests, such as size distribution and determination of void ratio and modulus of fineness of ash, their composition was verified by tests of nutrients. In the concrete, were carried out mechanical tests on bodies-of-proof being checked for compressive strength, diametral tensile and compression modulus of elasticity. The initial numbers showed significant results in tests for resistance to axial compression rates up to 20% replacement by mass of sand, recorded gains of up to 12% compared to the reference concrete, even with the sharp increase in the factor a / c . Thus, this research hopes to contribute to the implementation of the CBC as an alternative material in the production of Portland cement concrete, because it provides high resistance to 28 days with low consumption of cement.